THE STATE OF DEVELEPMENT STUDENTS’ SOCIAL ACTIVITY - RIDKODUBSKA, Hanna (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2023)
The article is dedicated to theoretically substantiating key aspects of the social activity development among students pursuing education in the socio-economic field, and to experimentally assessing the level of social activity development among first-level (bachelor's) education seekers. Based on the analysis of scientific sources, the main forms of social activity manifestation in various spheres of personal social life are identified, including political, civic, cultural, creative, labor, communicative, and business activities. The article presents the outcomes of an experimental investigation designed to assess the level of social activity development among students at the bachelor's education level. The findings shed light on the students' social activity, revealing patterns, tendencies, and areas for potential enhancement. This research contributes to a better understanding of the dynamics of social activity development in the student population. The research identifies that social activity manifests in active life attitudes, civic positions, and national participation, involving interaction with the surrounding environment. This interaction is shaped through the social and volitional efforts of individuals during the implementation of planned activities. The article also presents the results of an experimental study conducted among first-level (bachelor's) education seekers. A questionnaire was used to investigate the desires and forms of support for the social activity of youth with a socio-economic profile of education. Additionally, the locus of control was determined using the method of O. Ksenofontova. According to the diagnostic results, the level of social activity development among students is at an average level. Most students exhibited an unstable need for social activity, demonstrating fluctuating emotional attitudes towards it, limited awareness of the concept of "social activity," and situational effectiveness in the socio-political sphere. To summarize, it can be stated that specific behavioral reactions, such as emancipation, grouping with peers, and enthusiasm, have already formed among students. Interaction with peers is a necessary element for achieving common goals, contributing to the development of social interaction skills, and shaping authority, locus of subjective control, and value orientations.